Magyar ephorusok a kora újkori peregrináció történetében - Oláh, Róbert (Studia Litteraria, 2026)
In this paper we focus on the supporting figures of the cavalier’s tour, which served to train young noblemen. In order to outline the role of the noblemen’s companions and educators (known as ephorus, praeceptor, prefect, Hofmeister, or moderator), we draw on data from three sources. The instructions written by the noble parents who employed them, the letters sent by and addressed to them by the parents, and some diary entries testify their role during the cavalier’s tour. Finally, we compile a list of ephoruses known from the previous literature from the mid-16th to the mid-18th century, together with a brief description of the cavalier’s tour.